When the hypermodernity leads to blindness: disquietness in Saramago - D'Antony, Jean Paul (Revista Desassossego, 2022)
In this article, our intention is to trace a brief, yet not shallow, mapping of some points of the novel Blindness (1995), by José Saramago, in order to establish a dialogue that allows us to problematize the sunk, shifting and intensely modified identities through a world that presents itself way too white. Since the work in question shows an apparent neutralization of differences and homogenization of time and spirit as a consequence of the uniformity caused by the blindness, our research will remain immersed in the paradox and the disquieted concept of hypermodernity (LIPOVETSKY, 2004), as well as the ephemeral (LIPOVETSKY, 1989), the Identity (Bauman, 2005), among other theoretical approaches that cooperate with the assimilation of the inexhaustible literary-philosophical corpus of the saramaguian novel.